LncRNA RWDD3 Facilitates Leydig Cell Steroidogenesis by Regulating the miR-1388-5p/NPY1R/cAMP Pathway in Yanshan Cashmere Goats - Meijing Chen; Xuejiao Yin; Chunhui Duan; Yuchun Xie; Chenghao Ji; Yong Wang; Yueqin Liu; Yingjie Zhang (Animals, 2025)
Prolactin is a polypeptide hormone that plays a critical role in male reproduction. However, the underlying mechanisms of prolactin-regulated testosterone secretion and the roles of lncRNAs in this process remain unclear. We performed a comprehensive analysis of the testicular tissues of cashmere goats with different prolactin levels by means of RNA-sequencing. Then, we constructed a lncRNA–miRNA–mRNA interaction network by integrating previously submitted testicular mRNA sequencing data. We identified a novel lncRNA named lncRWDD3 and investigated its effects on testosterone synthesis in the Leydig cells of cashmere goat. The primary Leydig cells were used to explore the biological function of lncRWDD3/miR-1388-5p/NPY1R in vitro. This study found that 200 ng/mL of prolactin achieved the highest testosterone secretion in Leydig cells. LncRWDD3 or NPY1R overexpression promoted cAMP levels, testosterone secretion, and related gene expression, while lncRWDD3 or NPY1R interference had the opposite effect. It was found that lncRWDD3 acts on miR-1388-5p as a ceRNA, and neuropeptide Y receptor Y1 (NPY1R) was confirmed to be a target of chi-miR-1388-5p. Our research shows that prolactin regulates the testicular function of cashmere goats via the lncRNA–miRNA–mRNA ceRNA network, and lncRWDD3 acts as a ceRNA to activate NPY1R/cAMP signaling via the sponging of miR-1388-5p in order to govern testosterone synthesis in the Leydig cells of cashmere goats. Our results provide insights for future studies on the molecular mechanism of the prolactin regulation of testicular function in goats.